2017
DOI: 10.1109/toh.2016.2646370
|View full text |Cite
|
Sign up to set email alerts
|

Haptics in Music: The Effects of Vibrotactile Stimulus in Low Frequency Auditory Difference Detection Tasks

Abstract: Access to the full text of the published version may require a subscription. This article has been accepted for publication in a future issue of this journal, but has not been fully edited. Content may change prior to final publication. Abstract-We present an experiment that investigated the effect of vibrotactile stimulation in auditory pitch discrimination tasks. Extra-auditory information was expected to have some influence upon the frequency discrimination of auditory Just Noticeable Difference (JND) detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The vibrating glove was a replication of the glove used by Young et al (2017) and was equipped with six independent audio-haptic voice-coil exciters. The voice-coil transducers (TEAX14C02-8 Compact Audio Exciter) had a diameter of 14 mm and were designed to deliver vibrotactile output.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vibrating glove was a replication of the glove used by Young et al (2017) and was equipped with six independent audio-haptic voice-coil exciters. The voice-coil transducers (TEAX14C02-8 Compact Audio Exciter) had a diameter of 14 mm and were designed to deliver vibrotactile output.…”
Section: Methodsmentioning
confidence: 99%
“…To examine whether such discrimination enhancements extended to multisensory processing, Young et al (2017) used a two-alternative forced choice task in which participants had to determine whether a pair of stimuli were the same or different. Participant could hear the stimuli, combined or not with a corresponding tactile stimulation transmitted through a glove.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50Hz to 700Hz). Therefore, vibrotactile and auditory information can be naturally perceived as an interleaved signal, which is then also processed in partially shared brain regions, in both hearing participants as well as in congenitally deaf [29,30,31,32,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…JND studies have found applications in various areas of psychophysics including sound perception such as music and speech [27], visual perception [2,11], and haptics [8,12,27]. In this work, we narrow the focus of our attention to visual perception, specifically the perception of image quality.…”
Section: Introductionmentioning
confidence: 99%